Identification and gene expression analysis of genes encoding lactose permease and β- galactosidase in the Basidiomycota yeast Papiliotrema laurentii - Assis, João Victor Marques Gonçalves (2024)
Ricotta whey, an effluent generated by the dairy industry during the ricotta cheese manufacturing, is rich in the disaccharide lactose. Our research group recently isolated from soil the oleaginous yeast Papiliotrema laurentii UFV-1, which grows and produces lipids from this effluent, paving the way toward its application in third-generation biodiesel production. Nevertheless, increasing lipid production parameters is pivotal to make the bioprocess feasible. Over the last years, metabolic engineering has contributed to enhance the fermentative performance of yeasts in bioprocesses. However, improving lipid production by P. laurentii UFV-1 through metabolic engineering strategies is not a trivial task, as the proteins involved with lactose metabolism are so far unknown. Therefore, the identification of the genes responsible for lactose metabolism in P. laurentii UFV-1 is required for applying metabolic engineering strategies to increase lipid production on lactose-rich substrates, such as ricotta whey. Thus, this study aimed to identify and analyze the expression of the genes encoding putative lactose permeases and the β-galactosidase enzymes in P. laurentii UFV-1. By using bioinformatics tools, we identified the genes encoding lactose permease (Papla_5974) and β-galactosidase (Papla_5976). Surprisingly, we also identified a transcription factor gene (Papla_5975) between both genes. The three genes are on the same chromosome near each other, constituting a gene cluster. To evaluate the expression of these genes, we cultivated P. laurentii UFV-1 in Yeast Nitrogen Base (YNB) medium containing glucose, galactose, or lactose as the sole carbon sources. Besides, we cultivated this yeast in a YNB medium containing two carbon sources: glucose and lactose, and glucose and galactose. We quantified the gene expression via RT-qPCR at different growth stages. The lactose permease gene was induced in the presence of both lactose and galactose; otherwise, the β- galactosidase gene was induced only by lactose. For instance, it is unclear whether the transcriptional factor is involved in the activation of the genes encoding lactose permease and β-galactosidase. Notably, the expression of the transcriptional factor increased in the late stationary phase for glucose and lactose; thus, it may play a role under nutrient-limiting conditions. Furthermore, P. laurentii UFV-1 exhibited diauxic growth, which is consistent with the repression of the lactose permease and β-galactosidase genes by glucose in cultivations with glucose plus lactose and glucose plus galactose. Therefore, we describe for the first time a cluster of genes related to lactose metabolism in a Basidiomycota yeast, opening perspectives to improve lipid production by lactose-based media such as ricotta whey. Keywords: Ricotta whey. Lactose. Oleaginous yeast. Lipid production. Cluster genes